REPRESENTATION OF BASIC EMOTIONS OF CHARACTERS IN JUMBO CHILDREN'S ANIMATED FILMS A STUDY OF LITERARY PSYCHOLOGY THEORY OF PAUL EKMAN - Erlin Atifah Azzahrah; Elen Inderasari (Vol. 3 No. 1 (2025): Proceeding of International Conference on Cultures & Languages 2025, 2025)
Animated films are often considered an effective educational medium in helping children understand and appreciate the importance of managing emotions in daily life. The Jumbo film is an example of an animated film in which there is one of the characters who experiences various forms of basic emotions. Basic emotions are a form of psychological response that arises directly as a result of stimuli, both from the environment and from birth in children. This study aims to describe the basic emotional form of the main character in the Jumbo animated film using a literary psychology approach, based on Paul Ekman's theory of basic emotions, namely sad, angry, surprised, afraid, disgust, and happy. In addition, this study also aims to analyze the educational value of the characters contained in the film. The research method used is qualitative descriptive. The data source was obtained from video footage, scenes, and expressions of the main characters in the Jumbo film, with data collection techniques namely recording, observation, and repetitive footage techniques. The technique of checking the validity of the data in the form of source triangulation techniques and data analysis techniques is carried out using the steps as stated by Moleong, (2022). The analysis process is carried out through: identifying the dialogues, expressions, and actions of the main characters in the Jumbo film that show emotions; classifying the data into six basic emotions according to Paul Ekman; interpreting the meaning of these basic emotions to find the educational value of the characters contained in them. From the data found, there were fifty-two data consisting of six classifications of basic emotions, namely basic emotions of sadness in the form of sadness due to the loss of nine data, sadness due to disappointment two data, sadness due to despair two data, and sadness due to regret three data; basic emotions of anger, the types are anger at the loss of two data, anger directly or spontaneously one data, defensive anger one data, and prejudiced anger five data; basic emotions are surprised, in the form of spontaneity seven data; basic emotion of fear is in the form of realistic fear two data and neurotic fear one data; underlying emotions are insulting in the form of irritation one data; Happy basic emotions are in the form of happy joy two data, happy joy nine data, happy satisfaction three data, and happy enthusiasm two data. In addition, four character education values were also found that are in line with the Ministry of National Education, namely the value of responsibility, the value of hard work, the value of friendship, and the value of social care. With the results of this research, children can be introduced to the concept of basic emotion management and the application of good character education values.